Pengaruh Kegiatan Outbound Terhadap Kemampuan Motorik Kasar Pada Anak Kelompok B Di Tk 02 Ngemplak Karangpandan Karanganyar Tahun Ajaran 2016/2017 - Kiki Febriana, Ayu, Drs.Haryono Yuwono, S.E, M.Pd (2017)
Ayu Kiki Febriana/ A520120037; THE INFLUENCE OF OUTBOUND ACTIVITY TO WARD GROSS MOTOR SKILLS IN CHILDREN OF GROUP B AT TK 02 NGEMPLAK KARANGPANDAN KARANGANYAR, IN THE ACADEMIC YEAR OF 2016/2017 Research Paper, Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, March, 2017 The purpose of this study is to determine the effect of outbound activity against gross motor skills in children of group B at TK 02 Ngemplak Karangpandan Karanganyar, in the academic year of 2016/2017. This research method was quantitative method using a kind of experimental research with pre-experimental research design. Pre-experimental research design used one group pre-post test design. This study was conducted at TK 02 Ngemplak Karangpandan Karanganyar with 20 childrens for respondent. The data collection technique in this research was conducted through participant observation, documentation and test. The results of the data analysis used the comparative magnitude of "t" obtained after the calculation (t0 = 28.4507). It can be seen that t0 is greater than tt, namely: 2,09 <28.4507> 2.86. Because t0 was greater than tt then the null hypothesis was rejected. The conclusion of this study is that there is the influence of outbound activity to ward the gross motor skills in children. Keywords: Outbound Activities, Gross Motor Skills